2014
DOI: 10.1086/676922
|View full text |Cite
|
Sign up to set email alerts
|

Home Sweet Messy Home: Managing Symbolic Pollution

Abstract: Hanging up our coat, tidying our desk, classifying our books, what meanings do these mundane practices convey? Extending Mary Douglas's work, this article investigates tidiness from the angle of symbolic pollution. Based on photo-elicitation, it shows that, similarly to symbolic pollution described at a macro-social level, tidiness depends on two conditions, namely, a set of classifications and the dangerous transgression of these classifications. However, at a micro-social level, individuals negotiate boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 90 publications
(115 reference statements)
1
41
0
4
Order By: Relevance
“…Domesticity is reproduced in the home through practices creating conventional meanings of comfort, order, and efficiency (Dion, Sabri, and Guillard 2014). The convenient and easy cleaning of homes, bodies, and possessions depends on a material configuration of cheap and abundant water (Shove and Warde 2002).…”
Section: Embedded Securitymentioning
confidence: 99%
“…Domesticity is reproduced in the home through practices creating conventional meanings of comfort, order, and efficiency (Dion, Sabri, and Guillard 2014). The convenient and easy cleaning of homes, bodies, and possessions depends on a material configuration of cheap and abundant water (Shove and Warde 2002).…”
Section: Embedded Securitymentioning
confidence: 99%
“…For instance, they use the word to explain authentic Indian/Pakistani food/recipes. Being mindful of this fact, the translation was checked amongst the co-authors, who foreignized the translation, as suggested by Dion et al (2014). We tried to keep the tone of the statements the same and used some of the Hindi/Bengali words (e.g.…”
Section: Selfie Appropriationmentioning
confidence: 99%
“…Overall, despite attempts to better define diagnostic criteria for hoarding, critics of psychiatric definitions assert that many cases remain necessarily ambiguous (Maycroft, 2009). Hoarding and clutter must be understood as socially constructed problems that reflect, in part, the culturally negotiated meanings of home and tidiness (Cherrier & Ponnor, 2010;Dion, Sabri, & Guillard, 2014;Miller, 2008Miller, , 2011Young, 2002).…”
Section: Residential Clutter and Hoarding Disordermentioning
confidence: 99%